Cultura tributaria y su incidencia en el cumplimiento de las obligaciones en la declaración del impuesto al valor agregado y del impuesto a la renta de los pequeños negocios del sector urbano del cantón Pichincha provincia de Manabí periodo 2011-2012”. Plan de capacitación - Ponce Quijije, Fabricio Antonio (2013)
The present research is to evaluate the incidence of compliance statements Vat (VAT) and Income Tax in small commercial establishments Pichincha Canton of the province of Manabi period 2011-2012, given the little tax culture in some cases due to ignorance, lack of use of technology, little interest in the performance of their duties, among others. This research aims to improve the knowledge levels of the taxpayers of small commercial establishments thus increase the tax culture and thus prevent these businesses are affected by the sanctions incurred in breach of the same It has been established that the urban sector of Pichincha has 219 small commercial establishments such as: Drugstores, tercenas, hardware stores, grocery stores and others, using the formula of sampling was determined that the sample size will be 139 investigated establishments provided information to achieve the objectives. For the development of this research we used the inductive-deductive method, descriptive and exploratory, given the investigative techniques such as observation, survey, interviews, statistics and literature, getting to know everything about the subject. The study in the analysis and projection of the problem, and analyze the assumptions made, is sought within the same design a training plan and tax advice for small business establishments Pichincha Canton. From the initial research resulted that most people are unaware of the procedures for compliance with the state through tax administration, so a low level of tax culture. Favorable result was obtained with the proposed training plan and tax advice as it has the welcome and support of taxpayers in meeting their obligations and keep up with tax administration.